2019
DOI: 10.2141/jpsa.0170118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Lycopene or Tomato Paste on Laying Performance and Serum Lipids in Laying Hens and on Malondialdehyde Content in Egg Yolk upon Storage

Abstract: The present study was undertaken to investigate the effect of dietary, synthetic lycopene or tomato paste on laying performance and egg qualities in laying hens, and on lipid oxidation of stored eggs. One hundred and sixty 38-week-old Hy-line Brown laying hens were randomly housed in cages (two birds per cage, five cages per replicate) equipped with nipples and a trough-type feeder and subjected to one of four experimental diets. Each treatment had four replicates. A corn and soybean meal base diet was added w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 31 publications
5
22
2
Order By: Relevance
“…The average of eggshell thickness in this study ranged from 0.409 to 0.430 mm, and the eggshell strength ranged from 3.43 to 4.62 kg/cm 2 . These results were similar to that reported by An et al (2019) who found eggshell thickness and eggshell strength of eggs from laying hens fed with lycopene or tomato paste were 0.35-0.36 mm and 4.39-4.74 kg/cm 2 , respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The average of eggshell thickness in this study ranged from 0.409 to 0.430 mm, and the eggshell strength ranged from 3.43 to 4.62 kg/cm 2 . These results were similar to that reported by An et al (2019) who found eggshell thickness and eggshell strength of eggs from laying hens fed with lycopene or tomato paste were 0.35-0.36 mm and 4.39-4.74 kg/cm 2 , respectively.…”
Section: Resultssupporting
confidence: 91%
“…The inclusion of boiled tomato waste powder in laying hens diet did not affect Haugh unit, eggshell thickness, and eggshell strength of laying hens (Table 3). It has been reported that the inclusion of lycopene in laying hens diet did not have an effect on the Haugh unit (Honda et al, 2019;An et al, 2019). The average Haugh unit of laying hens in this study ranged from 69 to 81.…”
Section: Resultsmentioning
confidence: 51%
“…Only carotenoids that do not have provitamin activity, including lycopene (Imran et al, 2020) and astaxanthin (Davinelli et al, 2018), are able to accumulate in chicken egg yolks, while β-carotene is transformed into vitamin A, which although it enters the yolks of chicken eggs, does not affect their colour (Shevchenko et al, 2017a). Feeding laying hens with oil extracts of lycopene and astaxanthin in different doses for 90 days did not affect the indicators characterizing their quality, namely egg weight, albumen height, Haugh unit, strength and shell thickness, which is consistent with the results of studies by An et al (2019). Previous studies have also shown that carotenoids on the example of β-carotene have a positive effect on the morphological parameters and chemical composition of quail eggs (Shevchenko et al, 2017b).…”
Section: Discussionsupporting
confidence: 86%
“…In particular, there was a significant interaction between the effects of breed and diet on lutein content, which showed that the combination of MA dietary treatment and the SF breed resulted in a higher accumulation of lutein in the yolk. Feeding lutein to laying hens enhances hepatic SOD activity (Jang et al, 2014), while feeding them with lycopene increases yolk oxidative stability (An et al, 2019). The present study revealed similar findings, although the carotenoid types were dissimilar.…”
Section: Discussionsupporting
confidence: 79%